The Development of CLO3D Software E-Module for Digital Creation of Party Attire Patterns And Designs - Kosasih, Yeny; Sutopo, Yeri; Wahyuningsih, Sri Endah (Universitas Negeri Semarang, 2023)
The implementation of Pattern Making learning is closely tied to exploratory understanding, aiming to produce digital patterns and designs for party attire in accordance with the desired theme. Limited book references and modules, along with the scarcity of teaching media, have led to a low level of student comprehension regarding the learning material. The objective of this research is to develop an e-module using CLO3D software for creating digital patterns and designs for party attire. This study follows the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) RD development type. The instruments employed include a questionnaire to assess the e-module's levels of feasibility, practicality, and effectiveness. Feasibility testing data sources involve media experts and fashion material experts. Practicality testing data sources encompass fashion program teachers and 36 students from class XI at State Vocational High School 1 Pringapus. Effectiveness testing data sources consist of 36 students from class XI B1 as the experimental group and 36 students from class XI B3 as the control group at Vocational High School N 1 Pringapus. Based on the data analysis results, the feasibility testing yielded a score of 4.40 (criteria: very feasible), practicality testing resulted in a score of 92% (criteria: very practical), effectiveness analysis produced a score of 79% (criteria: effective), and the significance test analysis showed that the N-Gain_Persen obtained a Sig (2-tailed) value of 0.000 (smaller than the significance level of 0.05). This indicates that the data is effectively and significantly distributed, thereby confirming its suitability for use.